THE SIMULATION OF THE ORBITAL EVOLUTION OF A PASSIVE HIGH-ORBIT FRAGMENT WITH LARGE SURFACE AREA - Bazyey, A. A. (Одеські астрономічні публікації, 2014)
The numerical integration of the motion equations of a passive high-orbit fragment with large surface area was performed accounting for the main gravitational perturbations of the Earth, Moon and Sun, as well as the solar radiation pressure. Based on the numerical model of motion in the near-Earth space that accounts for only the most powerful perturbations, a new method for de-orbiting artiﬁcial celestial bodies from high altitudes is suggested.